Development of purification platforms for immunoglobulin y using aqueous biphasic systems - Rocha, Ana Mafalda Rodrigues Almeida (2020)
With the increase of antibiotic-resistant microorganisms and diseases that are unresponsive to conventional drugs, it is imperative the development of alternative, economical and effective therapeutics. The use of biopharmaceuticals, and in particular antibodies/immunoglobulins, is a promising alternative over common synthetic pharmaceuticals. Among these, antibodies obtained from chicken egg yolk, namely immunoglobulin Y (IgY), can be obtained in high titers by non-invasive methods, opening the door to low-cost biopharmaceuticals. Nevertheless, the production cost of high-quality and high-purity IgY remains higher than other drug therapies due to the lack of cost-efficient purification techniques. Aiming at producing IgY that could ultimately be used as a recurrent and widespread biopharmaceutical, this work is focused on the selective extraction of IgY from egg yolk using aqueous biphasic systems (ABS) as alternative purification platforms. Since egg yolk is a complex matrix, a first step including the lipids/lipoproteins precipitation and the water-soluble protein fraction (WSPF) recovery is required. The WSPF was recovered and characterized by mass spectrometry (LC‑MS/MS) and the main proteins identified (IgY, serum albumin (α-livetin), ovalbumin, ovotransferrin, vitellogenin 1 and vitellogenin 2). ABS composed of ionic liquids (ILs) and polymers or salts were initially investigated to purify IgY from the egg yolk WSPF, namely ABS composed of biocompatible and self-buffering ILs and PPG 400 (poly(propylene) glycol) or K3C6H5O7. This study allowed to conclude on the ILs cation and anion, and polymer and salt effects on the selective extraction of IgY to one of the ABS phases. Subsequently, polymer-salt-based ABS were investigated, namely ABS composed of PEG (polyethylene glycol) and Na2SO4 or phosphate salt buffer (K2HPO4/ KH2PO4, pH 5.5 - 8.0). These systems were also applied in centrifugal partitioning chromatography (CPC) while foreseeing the technology scale-up. The effect of the molecular weight of PEG, pH, mixture composition of the ABS, and CPC operating conditions (mobile phase flow rate, rotation, and the operation mode) were evaluated. The IgY stability/activity in various aqueous solutions of ILs, salts, and polymers was assessed. The best results regarding purity and yield of IgY were obtained with polymer-based ABS. In particular, the ABS composed of 18 wt% PEG 1000 + 13 wt% phosphate buffer at pH 6.0 allows obtaining IgY with a purity of 39% and yield of 100% in a single step. By the application of this ABS in CPC, IgY with a purity of 51% was obtained